1996
DOI: 10.5511/plantbiotechnology1984.13.311
|View full text |Cite
|
Sign up to set email alerts
|

Starvation Treatment Increases Transient Expression Frequency of a Foreign Gene Introduced into Eustoma grandiflorum Root Tissues by Particle Bombardment.

Abstract: Root explants of Eustoma grandiflorum were bombarded with plasmid pBI221 harboring the uidA gene encoding 9-glucuronidase (GUS) driven by a cauliflower mosaic virus 35 S promoter, and the effects of pre-and post-bombardment culture in various starvation media on the number of blue spots of GUS-expressing cells were studied. It was found that pre-and post-bombardment culture in nitrogen-depleted media increased the expression frequency of the transgene, by 4-to 8-times that of the control, and that 3-h pre-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Moreover, in another study on Lilium, MS medium free of NH 4 NO 3 , KNO 3 , and CaCl 2 improved transformation e ciency to 25.4% [20]. In Eustoma grandi orum, 4 to 8 times higher expression frequency was observed when nitrogen-depleted medium was used for cocultivation [31]. Furthermore, Shara et al indicated that removal of NH 4 NO 3, KH 2 PO 4 and KNO 3 signi cantly increased the transformation e ciency of Papaver bracteatum to 34.3% [32].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in another study on Lilium, MS medium free of NH 4 NO 3 , KNO 3 , and CaCl 2 improved transformation e ciency to 25.4% [20]. In Eustoma grandi orum, 4 to 8 times higher expression frequency was observed when nitrogen-depleted medium was used for cocultivation [31]. Furthermore, Shara et al indicated that removal of NH 4 NO 3, KH 2 PO 4 and KNO 3 signi cantly increased the transformation e ciency of Papaver bracteatum to 34.3% [32].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in another study on Lilium, MS medium free of NH 4 NO 3 , KNO 3 , and CaCl 2 improved transformation efficiency to 25.4% [ 25 ]. In Eustoma grandiflorum , 4 to 8 times higher expression frequency was observed when nitrogen-depleted medium was used for co-cultivation [ 42 ]. Furthermore, Sharafi et al indicated that removal of NH 4 NO 3, KH 2 PO 4 and KNO 3 significantly increased the transformation efficiency of Papaver bracteatum to 34.3% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%